A Strain of Siniperca chuatsi Rhabdovirus Causes High Mortality among Cultured Largemouth Bass in South China. Issue 3 (5th August 2013) - Ma, Dongmei; Deng, Guocheng; Bai, Junjie; Li, Shengjie; Yu, Lingyun; Quan, Yingchun; Yang, Xiaojing; Jiang, Xiaoyan; Zhu, Zemin; Ye, Xing
Abstract: In April 2011, 40% mortality of Largemouth Bass Micropterus salmoides juveniles occurred at a farm of Zhongshan City, Guangdong Province, China. Infected fish became lethargic, exhibited corkscrew and irregular swimming, and developed a distended abdomen and crooked body. Fish began to die within 2 d after the appearance of clinical signs. In order to analyze the pathogeny and diagnose the disease earlier, observation of clinical signs, cell infection, titer calculation, electron microscopy, immersion infection assay for fish, and nucleotide sequence analysis were carried out. Fathead minnow (FHM) cell cultures, inoculated with filtrate of liver and spleen homogenates from the diseased fish, developed the obvious cytopathic effect 46 h after inoculation in the primary culture and 24 h at the first passage. Typical rhabdovirus particles, 115–143 nm in length and 62–78 nm in diameter, were observed in infected FHM cells by direct transmission electron microscopy. The isolated virus produced a titer of 10 7.15 TCID50/mL. Immersion‐Fish infected with the virus had similar clinical signs and 80% mortality with 10 2.5 LD50/mL. The data indicated that the rhabdovirus was the lethal pathogeny of the current disease. Based on nucleoprotein‐gene nucleotide sequence multiple alignment analysis, the newly isolated virus is a strain of Siniperca chuatsi rhabdovirus (SCRV) under family Rhabdoviridae, which was initially isolated from Mandarin Fish Siniperca chuatsi . Up to the present, at least four virus strains have been isolated from diseased Largemouth Bass, which have had different clinical signs. Comparison of the clinical signs can help in an early diagnosis of the disease. Received October 30, 2012; accepted April 19, 2013